Outcome of IVF Treatment of Couples Attending the HOPE and Lab Aid IVF Clinic, Dhaka (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Infertility is a major reproductive health issue affecting millions of couples globally, with  significant psychological and social implications. Estimates suggest that 15% of couples experience infertility in South  Asia, including Bangladesh. Despite advances in assisted reproductive technologies (ART), particularly in vitro  fertilization (IVF), there is a lack of comprehensive data on the demographics and clinical characteristics of couples  seeking these services in Bangladesh. This study aimed to evaluate the demographic and clinical profiles of couples  undergoing IVF treatment at IVF Clinics in Dhaka to assess the treatment outcomes.  Methods: This cross-sectional observational study was conducted from January to December 2024, enrolling 126  couples aged 18 to 45 years seeking IVF due to primary or secondary infertility. Participants completed a structured  questionnaire capturing demographic information, infertility history, clinical assessments, and IVF treatment protocols.  Couples were excluded if they had anatomical abnormalities requiring surgical intervention, previous IVF treatment at  another facility, or significant medical comorbidities. Data analysis involved descriptive statistics to summarize  demographic and clinical characteristics, and outcomes such as clinical pregnancy rates and live birth rates were  recorded.  Results: The study revealed that participants had a mean age of 32.6 years, with approximately 40% aged 20 to 30  years and 41.3% aged between 30 and 40 years. Over 70% of participants experienced primary infertility, with the  average duration of infertility being 8.9 ± 4.4 years. Common reasons for delaying IVF included a lack of knowledge  (44.4%) and inadequate resources (23.8%). Following IVF, the overall pregnancy test positivity rate post-IVF was  37%, and more than one-third (35.7%) of cases showed a gestational sac on ultrasound. Over one-third (37.3%)  achieved clinical pregnancy, with 21(44.6%) progressing to full-term pregnancies, leading to 19 singleton births and  2 multiple births. Of the conceived cases, there were 13(27.7%) spontaneous abortions and 9(19.1%) instances of  blighted ovum. Additionally, 3 cases (6.4%) resulted in preterm labor, and 3(6.4%) were ectopic pregnancies.  Conclusion: This study highlights key demographic and clinical features of couples undergoing IVF treatment in  Dhaka, Bangladesh, revealing a high prevalence of primary infertility and significant barriers to accessing IVF due to  limited knowledge and resources. While the conception rate is acceptable, the success rates are notably lower than  global averages, indicating a need for further research to improve IVF outcomes for couples struggling to conceive. Ibrahim Card Med J 2024; 14(1): 28-34